Cognitive Behavioral Therapy in Children and Adolescents with Anxiety Disorder - Emel KARAKAYA; Didem Behice ÖZTOP (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Currently, Cognitive Behavioral Therapy (CBT) becomes one of the leading approaches in the psychotherapy. However, use of CBT in childhood psychotherapy is considerably novel. After 1990s, it has been understood that it is an effective method for children and adolescents. Anxiety disorders are one of the most common problems in the field of childhood and adolescent psychiatry. In the studies conducted, the effectiveness of CBT was demonstrated in anxiety disorders of the children and adolescents. Moreover, it was suggested that this effectiveness is permanent in some studies. Priority goal of CBT is to change inappropriate learning and thinking patterns in the children and adolescents. By “now and here” fashion, it is attempted to reveal the origin of current problems. During the process, the factors are considered, which cause to maintain the symptoms. It is attempted to decrease signs caused to stress by improving coping skills during therapy. To this end, methods including observation, relaxation training, systematic desensitization, social skills training, cognitive restructuring and exposure therapy are applied in sessions by taking child’s problems into consideration. Scales specific to anxiety disorders are used in the assessment and follow-up. Age and development level of the child should be particularly taken into account while using assessment tools and therapeutic modality [JCBPR 2013; 2(1.000): 10-24]